2014
DOI: 10.1002/polb.23537
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric behavior and polarization mechanism in odd‐odd polyamide 11,11

Abstract: Ferroelectric and piezoelectric behavior in odd‐odd polyamide 11,11 are successfully detected for the first time. The maximum coercive field (Ec) of 90 MV/m, and a remnant polarization (Pr) of 40 mC/m2 are obtained at room temperature. A piezoelectric strain coefficient (d33) value as high as −3.9 pC/N has been found in stretched polyamide 11,11 film. The structural change of samples before and after poling is investigated by wide‐angle X‐ray diffraction patterns, differential scanning calorimetry, and Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…The melting points are found at 180.3, 183.3, and 179.3 C for nylon 11-11, nylon 9-13, and nylon 11-13, respectively. These melting points are comparable to the values reported in the literature of 180.1 C for nylon 16 182 C for nylon 9-13, 18 and 176 C for nylon 11-13. 18 In addition to these major peaks due to melting, small double peaks were observed before the main major melting peaks, as shown in Figure 1 (b,c).…”
Section: Resultssupporting
confidence: 89%
“…The melting points are found at 180.3, 183.3, and 179.3 C for nylon 11-11, nylon 9-13, and nylon 11-13, respectively. These melting points are comparable to the values reported in the literature of 180.1 C for nylon 16 182 C for nylon 9-13, 18 and 176 C for nylon 11-13. 18 In addition to these major peaks due to melting, small double peaks were observed before the main major melting peaks, as shown in Figure 1 (b,c).…”
Section: Resultssupporting
confidence: 89%
“…Nylons, or aliphatic polyamides, are important industrial materials due to their excellent physical properties which include high strength, abrasion resistance, ductility and good stability at high temperatures . Recent studies have also demonstrated that several nylons derived from odd units might be interesting for electroactive applications . The geometry and density of hydrogen bonds play a key role in the crystallization process, the crystalline structure and the final properties of nylons .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent studies have also demonstrated that several nylons derived from odd units might be interesting for electroactive applications. 3 The geometry and density of hydrogen bonds play a key role in the crystallization process, the crystalline structure and the final properties of nylons. 4 In general, nylons are semicrystalline polymers capable of adopting different crystalline structures depending on the number and parity of methylene groups of their repeat unit.…”
mentioning
confidence: 99%
“…Nylons 5 6 [3-6], 6 9 [7] and 13 6 [8] can be considered in this context. Furthermore, the ferroelectric behavior of odd numbered polyamides has been discovered, with remanent polarization being linearly dependent upon the dipolar density of amide groups [9,10]. Specifically, nylon 6 9 has also been considered as a material with piezoelectric activity due to its peculiar structure [7].…”
Section: Introductionmentioning
confidence: 99%